Paramedicine students’ experiences on placement: preparedness for the emotional impacts of witnessing trauma - Tim Michael; Laurie A. Chapin; Charlton D. Quitoriano (BMC Medical Education)
Abstract Paramedicine is a psychologically high-risk profession, with workers routinely exposed to fatalities and severe medical and emotional trauma. During their studies, paramedicine students undergo practical training with ambulance crews. Without experience, and often with limited emotional preparation, students are exposed to many of the same graphic and traumatic situations as working professionals. This qualitative social constructionist study explored the emotional impacts experienced during placement and students’ emotional preparedness to cope with the challenges of placement. Findings revealed a range of significant emotional impacts reported by the participants. Initial anxiety was found to intensify the response to distressing incidents involving fatalities, severe injuries, domestic violence, and suicide-related incidents. In some cases, students reported ongoing, lingering emotional effects. Most students also felt that they were inadequately prepared for the emotional challenges of placement. A common recommendation among the participants was the inclusion of formal mental health education and resilience training prior to placement. Given the prior absence of research exploring the lived experiences of paramedic students on placement, the current findings add important depth and a student perspective. The implications of this research highlight an urgent need for a greater focus on students’ emotional preparedness prior to placement training.